The five senses: smell - Parramon, Jose Maria (New York : Barron's Educational Series, Inc, 1985)
A short scientific explanation of our sense of smell, with a diagramof the nose.
Translationof: Los cinco sentidos-el olfato
Keywords: Smell-Juvenile literature; Smell; Nose; Senses and sensation